A Rare Case of Symptomatic Double Optic Disc Pit without Maculopathy - Zaria Ali; Mohammad Abdul-Nabi (Case Reports in Ophthalmological Medicine)
Optic disc pits are an uncommon congenital abnormality. Patients remain asymptomatic unless they develop maculopathy. We present a rare case of a double optic disc pit of which only three others have been reported worldwide. A 51-year-old gentleman presented with blurred vision. Fundoscopy revealed a right double optic disc pit. Though he was symptomatic there was no evidence of maculopathy. OCT of macula and disc was otherwise unremarkable. Visual field demonstrated a paracentral defect. Although optic disc pits are rare they are still an important clinical entity. Prompt identification and treatment of complications are required to prevent a poor visual prognosis.